A Lifetime of Catalytic Micro-/Nanomotors - Tao He; Yonghui Yang; Xuebo Chen (Nanomaterials)
Microscopic and nanoscopic motors, often referred to as micro-/nanomotors, are autonomous devices capable of converting chemical energy from their surroundings into mechanical motion or forces necessary for propulsion. These devices draw inspiration from natural biomolecular motor proteins, and in recent years, synthetic micro-/nanomotors have attracted significant attention. Among these, catalytic micro-/nanomotors have emerged as a prominent area of research. Despite considerable progress in their design and functionality, several obstacles remain, especially regarding the development of biocompatible materials and fuels, the integration of intelligent control systems, and the translation of these motors into practical applications. Thus, a comprehensive understanding of the current advancements in catalytic micro-/nanomotors is critical. This review aims to provide an in-depth overview of their fabrication techniques, propulsion mechanisms, key influencing factors, control methodologies, and potential applications. Furthermore, we examine their physical and hydrodynamic properties in fluidic environments to optimize propulsion efficiency. Lastly, we evaluate their biosafety and biocompatibility to facilitate their use in biological systems. The review also addresses key challenges and proposes potential solutions to advance their practical deployment.